Validation of the Rapid Diagnostic Test for Dengue Fever/Dengue Hemorrhagic Fever which Detecting both Antigen and Antibody - สติมัย, วิชัย; บัวล้อมใบ, พงษ์วิทย์; วุฒิธนโชติ, วิบูลย์ศักดิ์; รอดนาค, ฑิตถากร; คงพ่วง, คนึงนิจ; ทิพย์มนตรี, รุ่งระวี (Disease Control Journal, 2011)
The objective of this study was to evaluate the rapid diagnostic test for Dengue and Dengue haemorrhagic fever (DF/DHF) which detecting RDT NS1 and RDT IgM/IgG (SD Bioline Dengue Duo). One hundred and seventy - three suspected DF/DHF cases from Chumpae Community Hospital, Khon Kean Province, Thailand during July - September 2009 were recruited into this study. The results showed this rapid diagnostic test detected 40 and 23 primary and secondary infective patients respectively. The sensitivity was 70.4 % and specificity was 89.9 % in acute phrase of illness while in convalescence phase, the sensitivity and specificity were 77.3 % and 86.3 % respectively. Totally, the test gave 71.4 % sensitivity and 88.9 % specificity to all patients. However, the RDT's sensitivity was deviated by the duration after onset of fever. The RDT NS1 showed the highest sensitivity in the third day ( 100 %) and the RDT IgM showed the highest sensitivity in the forth day ( 58 %). This rapid diagnostic test showed moderate sensitivity; nevertheless, it showed high specificity in both acute and convalescence phases of illness. In addition, its sensitivity showed the highest in the early phase of illness (the 3rd - 4th day after onset of illness).